1999
DOI: 10.1111/j.1469-7793.1999.101af.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal agonist stimulation results in spatially restricted Ca2+ release and capacitative Ca2+ entry in bovine vascular endothelial cells

Abstract: Ca¥ release was initiated at the site of stimulation and frequently propagated some tens of micrometres into non-stimulated regions. Local Ca¥ release caused activation of capacitative Ca¥ entry (CCE). CCE was initiallycolocalized with Ca¥ release. Following repetitive focal stimulation, however, CCE became detectable at remote sites where no Ca¥ release had been observed. In addition, the rate of Ca¥ store depletion with repetitive local activation of release in Ca¥-free solution was markedly slower than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…On the other hand, ATP induces Ca 2+ i responses both in early and organized tubules in vitro. In contrast to AA, ATP binding to its specific G-protein -coupled P2Y receptors triggers a strong and fast Ca 2+ release from intracellular stores via IP3 production, followed by a sustained store-operated Ca 2+ entry (47). The lack of a tubulogenic effect and the unaltered ATP-induced Ca 2+ i signals during the capillary-like network development support the hypothesis of a specific role for AAinduced Ca 2+ i signals in the early steps of B-TEC in vitro angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ATP induces Ca 2+ i responses both in early and organized tubules in vitro. In contrast to AA, ATP binding to its specific G-protein -coupled P2Y receptors triggers a strong and fast Ca 2+ release from intracellular stores via IP3 production, followed by a sustained store-operated Ca 2+ entry (47). The lack of a tubulogenic effect and the unaltered ATP-induced Ca 2+ i signals during the capillary-like network development support the hypothesis of a specific role for AAinduced Ca 2+ i signals in the early steps of B-TEC in vitro angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of intracellular BAPTA to slow reloading, and of Ba 2+ and Mn 2+ , which are not transported by Ca 2+ pumps, to enter the cytosolic pool following store depletion, was taken as evidence that Ca 2+ entering the cell traverses a narrow gap of cytosol before being actively pumped into the ER [17]. Later studies of Xenopus oocytes, endothelial cells and astrocytes showed that local receptor stimulation evoked Ca 2+ entry (as detected by Cl − channel activation or Ca 2+ -dependent dye signals) that was confined to within 10's to 100's of μm from where Ca 2+ release was thought to occur [18][19][20][21].…”
Section: Communication Between Ca 2+ Stores and The Crac Channel: Locmentioning
confidence: 99%
“…The only available marker for active CRAC channels is the elevated [Ca 2+ ] i microdomains that form near open channels. Several prior studies using Ca 2+ -sensitive dyes have shown that SOCE occurs within 10-100 μM of the ER [19][20][21], but the applied imaging techniques lacked sufficient resolution to pinpoint the relationship between individual influx sites and junctional ER structures. Much higher resolution is possible with TIRF microscopy, which has been used to image Ca 2+ microdomains near voltage-gated Ca 2+ (Ca V ) channels on a submicron scale [67,68].…”
Section: The Dynamic Dyad: Defining the Elementary Unit Of Store-opermentioning
confidence: 99%
“…In calf pulmonary artery endothelial cells (CPAEs), elementary events precede the onset of the massive ATPinduced Ca 2+ release from intracellular stores, leading to the vasoactive response [5,6].…”
Section: Introductionmentioning
confidence: 99%